Australian prison vocational education and training and returns to custody among male and female ex-prisoners: A cross-jurisdictional study. Issue 1 (March 2019) - Cale, Jesse; Day, Andrew; Casey, Sharon; Bright, David; Wodak, Jo; Giles, Margaret; Baldry, Eileen
The current study examined the impact of vocational education and training in the custody setting on returns to custody among Australian adult prisoners from selected jurisdictions. Vocational education and training, education, and behavioural change programme participation in custody and demographic and risk assessment data were provided by correctional services in four Australian states for 10, 834 Australian prisoners released from custody in 2010–2011. This information was used to predict returns to custody by 2015–2016. Overall, the results showed that participating in vocational education and training in custody contributed to the likelihood of remaining custody free at two and five years post-release for both male and female prisoners. However, for males the relationship was moderated by risk level. These findings are discussed in the context of developing vocational education and training in prison settings to address the specific needs of individuals and expectation of the wider community.